Effect of sintering temperature on hydroxyapatite compact scaffold characteristics - Wassanai Wattanutchariya (2018)
© IEOM Society International. Hydroxyapatite (HA) is a bioceramics with composed of phosphate and apatite that a chemical composition similar to human mineral tissue. It can be synthesized from many natural sources with calcium-based structures, such as bovine bone, mollusk shell, silk cocoon, and coral. Currently, HA is commonly applied in medicine as a dentin bone or bone grafting substitute in orthopaedic surgery, and may be formed into an appropriate scaffold for implantation. Spark Plasma Sintering (SPS) is a new sintering technique, also known as field assisted sintering technique or pulsed electric current sintering, which can produce a dense structure from powder material. This study utilized the SPS process to fabricate the HA compact scaffold as well as investigated the effect of sintering temperature on the scaffold's physical and mechanical properties. The morphology and composition of the specimens were verified by scanning electron microscope (SEM) and X-ray diffraction (XRD). Density and hardness were evaluated using Archimedes's principle and the knoop hardness test, respectively. The results revealed that both density and hardness of the sintered specimen decreased when the sintering temperature increased. The maximum hardness of HA compact scaffold was 3.66 GPa when the sintering temperature was 1,000 °C, while the maximum density of scaffold was 3.07 g/cm3 at 1,050 °C. © IEOM Society International.